PENGARUH PERSEPSI MANFAAT, PERSEPSI KEPERCAYAAN DAN FITUR TERHADAP KEPUTUSAN MENGGUNAKAN BANK DIGITAL ALADIN DI KABUPATEN DAN KOTA PEKALONGAN PADA ERA NEW HABIT - Putri Nurul Amalia; Rohmad Abidin; Bambang Sri Hartono (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The COVID-19 pandemic requires banks to be able to provide electronic-based transactions, carry out digital transformation, and also open up opportunities for financial technology-based companies. An example of this transformation is the first Sharia-based digital bank such as Aladin Digital Bank. This study aims to analyze the effect of perceived usefulness, perceived credibility, and features on the decision to use Aladin Digital Bank in the Pekalongan Regency and City in the New Habit Era. This study uses primary data with 20 statement items distributed through Google Forms and questionnaires with quantitative methods to the people of the Pekalongan Regency and City who have used the Aladin Digital Bank application. The number of samples was 97 respondents using the purposive sampling method. The data analysis technique uses multiple linear regression analysis with the help of SPSS version 26 software with a significance level of 5%. The results showed that the perceived usefulness variable had a positive and significant effect partially, while the perceived credibility and feature variables had no positive and significant effect partially. However, the variables of perceived benefits, perceived trust, and features have a positive and significant impact simultaneously.